Rebuilding Jewish life in Germany - Geller, Jay Howard 1972-; Meng, Michael 1978- (Rutgers University Press, 2020)
"Featuring essays by scholars of history, literature, television, and sociology, Rebuilding Jewish Life in Germany illuminates important aspects of Jewish life in Germany since 1949, including institution building, the internal dynamics and changing demographics of the Jewish community, and the central role of Jewish writers and public intellectuals."--